2022
DOI: 10.1038/s41380-022-01533-7
|View full text |Cite
|
Sign up to set email alerts
|

Corticolimbic DCC gene co-expression networks as predictors of impulsivity in children

Abstract: Inhibitory control deficits are prevalent in multiple neuropsychiatric conditions. The communication- as well as the connectivity- between corticolimbic regions of the brain are fundamental for eliciting inhibitory control behaviors, but early markers of vulnerability to this behavioral trait are yet to be discovered. The gradual maturation of the prefrontal cortex (PFC), in particular of the mesocortical dopamine innervation, mirrors the protracted development of inhibitory control; both are present early in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 74 publications
(82 reference statements)
1
13
0
Order By: Relevance
“…Furthermore, the prefrontal cortex (PFC) serves as the chief executive officer of the brain, controlling the highest level of cognitive and emotional processes, which are commonly disrupted in mental illnesses, such as ADHD ( Hiser and Koenigs, 2018 ; Yan and Rein, 2022 ). Many studies of ADHD have reported volumetric abnormalities in PFC and indicated that ventromedial prefrontal cortex structure is a biomarker for ADHD symptomatology ( Albaugh et al, 2017 ; Bayard et al, 2020 ; Restrepo-Lozano et al, 2022 ). Aberrant serotonergic neurotransmission has long been implicated in the pathogenesis of neuropsychiatric disorders associated with PFC dysfunction, including schizophrenia, depression, and anxiety ( Leonardo and Hen, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the prefrontal cortex (PFC) serves as the chief executive officer of the brain, controlling the highest level of cognitive and emotional processes, which are commonly disrupted in mental illnesses, such as ADHD ( Hiser and Koenigs, 2018 ; Yan and Rein, 2022 ). Many studies of ADHD have reported volumetric abnormalities in PFC and indicated that ventromedial prefrontal cortex structure is a biomarker for ADHD symptomatology ( Albaugh et al, 2017 ; Bayard et al, 2020 ; Restrepo-Lozano et al, 2022 ). Aberrant serotonergic neurotransmission has long been implicated in the pathogenesis of neuropsychiatric disorders associated with PFC dysfunction, including schizophrenia, depression, and anxiety ( Leonardo and Hen, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, dopamine receptor over-expression in the dorsal striatum was confirmed to be independent of gonadal hormones in rats of both sex via gonadectomies ( Andersen et al, 2002 ). Adolescent dopamine receptor overexpression may be related to more recent reports of DCC-netrin-mediated dopaminergic axonal outgrowth, impulsivity, and behavioral response to addictive substances in male mice ( Reynolds et al, 2018 , Cuesta et al, 2020 , Restrepo-Lozano et al, 2022 ). As yet, there is no link between synaptic overexpression and immune signaling, but microglia are important for dopamine neuron axon outgrowth earlier in life ( Squarzoni et al, 2014 ).…”
Section: Pre-puberty Early Adolescencementioning
confidence: 83%
“…In a comparison with the Gene-Tissue Expression (GTEx) v8 eQTL catalogue 74 , the combination of these eQTLs associated with cyan module genes were highly specific to the placenta ( Figure S1D ). We then identified these variants in the children of the GUSTO cohort and weighted them based on their effect size from Peng et al , before summing them within individuals to create a fetoplacental PGS (as described previously 49,50 ). We reasoned that a PGS comprised of eQTLs would be representative of individual variation in cyan module expression.…”
Section: Resultsmentioning
confidence: 99%
“…PGS based on gene lists were generated as previously described [49][50][51] . In brief, SNPs located on genes in a relevant list were identified using the biomaRt package 52,53 .…”
Section: Pgs Generationmentioning
confidence: 99%